Compact Powell-Lens-Based Low-Coherence Correlation Interrogation System for Fiber-Optic Fabry-Perot Sensors - Zhibo Ma; Tongxin Guo; Tianyang Zhang; Wei Wang; Haibin Chen; Xiongxing Zhang; Weizheng Yuan (IEEE Photonics Journal, 2019)
For the absolute cavity length interrogation of fiber-optic Fabry-Perot (FP) sensors, a low-coherence interferometer based on the Powell lens is proposed and demonstrated. The usage of a large-fan-angle Powell lens combined with a tiny fiber collimator for achieving a line-type beam and uniform beam-profile distribution improves the power adaptability of the system for different types of fiber-optic FP sensors. Furthermore, the system volume is considerably reduced, rendering it more compact than the conventional system using a cylindrical lens or mirrors.